(untitled) (Journal of the College of Education for Women, 2019)
Abstract:This tribe had lived in Iraq since the first century A.D. Persia tried tokeep this tribe away from Iraq, but without result. The tribe managed to getvictory against Persia in the battle of Dhyqar.When the Muslims had come to conquer Iraq, Rabi’a welcomed themand takes part in that action.That tribe helped the caliph Ali in the Jammal and Sifffen wars in orderto remain Iraq the center of the Islamic caliphates this tribe had felt very sadand sorrowful when the caliphate become to the Umayyad . This tribe did notgive up, so this tribe did what could be done to help those who had revoltedagainst the Umayyad. Rabi’a did that in order to get ride of the Mudriat alsham,and favored Rabi’a side against them. That made Abid al-Malik tries toweaken Rabi’a, so he immigrated her alliance the Azdiate to Mosule where hisbrother was governor of the Jazira.Some parts of Rabi’a were Khawarij, but they did not believe in theideology of them. They did that in order to get ride of the Mudhariyat al-sham,who were acused that they were the responsible of killing the prophet family.Generally, Rabi’a had resisted the Umayyad caliphate because thecaliphate got close to Mudhariate al-sham and kept Rabi’a away, beside that the Umayyad caliphate gave the Mudhariate and Yamaniyyat al-sham, theprivileges that made their control on Iraq, the central of Rabi’a tribes.Basra and Kufa were the importance centers of Rabi’a those two centershad the top of the difference between the two alliances, Rabi’a’ and Azid onone side and Tamim, Quis on other side.It was noted that some of the Rabi’a who were among the Arbaa orAkhmas of Kufa and Basra, were beside the Umayyad caliphate in the naturalcircumstances. But when the caliphate become weak, these tribes helpedRabi’a against the Umayyad caliphate